Experimental Study Of The Hydraulic Efficiency Between A Depressed And A Non-Depressed Grate In Bandar Baharu, Kedah - Md Wakif, Sarah Alia (Universiti Sains Malaysia, 2018)
This research was performed in order to study the effect of the hydraulic efficiency of non-depressed gully grate inlet of a Malaysian drain. The location of the site study is located at the Bandar Baharu which is approximately 9.8 km from the USM Engineering Campus. Gully inlets help to convey water ponding on the pavement surface to the inlet system; hence a proper and adequate design is necessary to reduce the stagnant water on the pavement surface so that the drivers can drive comfortably and safely without any dangerous incidents. The study was conducted with the aim to compare the hydraulic efficiency between depressed to non-depressed gully grate system with different longitudinal bed slope and cross slope under different flow conditions. In order to determine the efficiency of the gully grate system at the site, a full scaled of physical model had been constructed to demonstrate the actual conditions occur. There are two types of gully system used in this study, terminal system and intermediate system. Terminal system does not permit the approaching flow to pass through the next downstream gully whereas the intermediate system permit the approaching flow to pass through the downstream gully system. The test was also conducted with different longitudinal slope and cross slope to demonstrate the real condition of the road pavement at the highways. The system was then upgraded by adding plywood at the inlet tank to increase the flow path. The data obtained was then compared to the old system (shorter flow path) to determine the differences between two systems in terms of efficiency and water depth. Lastly, results obtained from the study are presented in the form of head (pressure) - discharge relationship, hence the comparison of hydraulic efficiency of the gully grates were established.